2018
DOI: 10.1159/000493407
|View full text |Cite
|
Sign up to set email alerts
|

Panax Quinquefolium Saponins Attenuate Myocardial Dysfunction Induced by Chronic Ischemia

Abstract: Background/Aims: Previous studies in rat models of myocardial ischemia showed that Panax quinquefolium saponins (PQS) could attenuate ischemic/reperfusion injury, increase vessel density and improve cardiac function. In the current study, we examined whether PQS could attenuate myocardial dysfunction in a swine model of chronic myocardial ischemia (CMI). Methods: CMI was established in Bama mini-pigs by placing amroid constrictor on the left anterior descending artery (LAD). Starting from 2 months after the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In short, the pathogenesis of MIRI begins with calcium overload and oxidative stress caused by sudden changes in the environment ( 54 ). Calcium overload and oxidative stress interact with each other ( 55 , 56 ), resulting in the destruction of cell structure and function ( 57 , 58 ), leading to necrosis or apoptosis ( 1 ). The necrotic cells cause a different inflammatory response, stimulating other cells to start pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In short, the pathogenesis of MIRI begins with calcium overload and oxidative stress caused by sudden changes in the environment ( 54 ). Calcium overload and oxidative stress interact with each other ( 55 , 56 ), resulting in the destruction of cell structure and function ( 57 , 58 ), leading to necrosis or apoptosis ( 1 ). The necrotic cells cause a different inflammatory response, stimulating other cells to start pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PET imaging combined with proteomic analysis has been used to measure the heart's glucose uptake capacity during cardiopulmonary activity assessment. Guo et al found that panax quinquefolium saponins (PQS) can significantly improve cardiac function and glucose utilization, they also showed that PQS blocks neovascularization by affecting the expression level of protein kinase C delta (PRKCD), a target of PQS (Guo et al 2018 ). In another study, an analysis was performed using the rubidium-82 PET imaging results of the cardiac function and myocardial blood flow reserve for 97 patients.…”
Section: Applicationsmentioning
confidence: 99%
“…Based on our previous pharmaceutical studies, the major ingredients of SQSX can activate phosphatidylinositol 3-hydroxykinase-protein kinase B (PI3K-Akt) signaling pathyway and elevate the expression of VEGF mRNA in ischaemic myocardium of rats to promote neovascularization and angiogenesis ( 17 ). It can regulate the expression of Ang1/Tie2 and Ang2/Tie2 in hibernating myocardium and promote neovascularization and maturation to improve cardiac function ( 18 ). It's also proven that the ingredients of SQSX inhibit the proliferation of vascular smooth muscle cells in the in-stent restenosis minipig model induced by balloon injury, thereby preventing in-stent restenosis ( 19 ).…”
Section: Introductionmentioning
confidence: 99%